Effects of high‐molecular‐weight glutenin subunit combination in common wheat on the quality of crumb structure. (19th October 2018) - Jiang, Peihong; Xue, Jiesheng; Duan, Luning; Gu, Yunsong; Mu, Junyi; Han, Shichen; Chen, Lin; Li, Yaxuan; Ma, Wujun; Yan, Yueming; Li, Xiaohui
Abstract: BACKGROUND: High‐molecular‐weight glutenin subunits (HMW‐GSs) have important effects on bread‐making quality. Allelic variations of HMW‐GS in bread wheat varieties contribute in different ways to dough properties and bread volume. However, no systematic analysis has been done on the effects of allelic variation on bread‐crumb structure, an important parameter when evaluating bread‐making quality. In this study, seven Glu‐1 deletion lines and one intact line harboring different encoding loci and derived from a cross between two spring wheat cultivars were used to investigate the contribution of a single Glu‐1 locus, or combination of Glu‐1 loci, to the crumb structure. RESULTS: Deletion of HMW‐GS locus combinations resulted in a decline in slice size, brightness, and fineness of the bread crumb. A desirable crumb structure correlated well with preferred subunit combinations: high levels of GMPs, superior dough properties, and loaf volume. The effects of the HMW‐GS combinations were ranked as Dx5 + Dy10 > Bx17 + By18 > Ax1 + Null. The Ax1 + Null allele affected the crumb structure by interacting with the Bx17 + By18 or Dx5 + Dy10 . CONCLUSION: High‐molecular‐weight glutenin subunits had significant effects on the loaf volume and crumb structure; varying effects from different subunit combinations were observed. © 2018 Society of Chemical Industry